The introduction from a narrative perspective in the ’Smart book’ - Abdul Hussein, Dr. Hussein Ali; Karim, Lecture. Mayada Abdul Amir; Muhammad, Ass. Lecture Abbas Hazem (Thi Qar Arts Journal, 2023)
There is no doubt that the news is one of the closest narratives to the story, and people have transmitted the news in their first era until it became their companion and the fruit of their conversations, where the Arabs were passionate about narrating and documenting the news until many of those news documents reached us, many of which have not been studied yet, and Arab researchers in the modern era have paid attention to this huge narrative heritage that our ancestors left written in the folds of huge volumes, although most of it was lost and lost, and perhaps the development that has reached the methods of studying and criticizing narrative genres, which resulted in a science in itself, is “narrative science” One of the reasons for this attention. The narrative structure of the news consists of several elements, one of which complements the other in its introduction, which is the introduction that the research seeks to study in one of the Arabic news documents attributed to Ibn al-Jawzi and titled (The Smart), due to the importance that this narrative element is distinguished by being an effective element in The structure of the news is what begins with the narration and what first strikes the ears. The structure of the research was based on three demands. The first one stopped at the concept of both news and introduction, as the research is based on showing (the introduction) from a narrative perspective in a book (news), while the second demand defined the general structure of the book under study and showing the most prominent narrative characteristics in it. To end up with us at The third requirement, which was concerned with studying the introduction in this book, is a study that is consistent with modern narrative discourse.